The influence of road maintenance substances on the growth of graminaceous plants - Kazlauskienė, Agnė; Brukštutė, Vaida (Journal of Environmental Engineering and Landscape Management, 2015)
The article describes the experimental research on the effect of road maintenance materials on three species of graminaceous plants. The experiment was carried out using technical granular sodium chloride (NaCl) treated with potassium hexacyanoferrate – a road maintenance material most widely applied in wintertime in Lithuania. As an alternative, an organic material obtained on the basis of molasses, patented under the name of Safecote in Europe, was selected for the experiment. Three species of gramineous plants, most frequently used for roadside planting in Lithuania when building new and reconstructing or renovating the existing motor roads, were analysed: perennial ryegrass(Lolium perenne L.), meadow fescue (Festuca pratensis Huds.), and common meadow-grass (Poa pratensis L.).The paper presents experimental findings regarding the effect of road maintenance materials on the parameters of graminaceous plants – the height of the above-ground part and phytomass.